Odpowiedzi

2010-02-11T20:58:08+01:00
X+4y=-2
3x-8y=10

x= -2 - 4y
3 * (-2 - 4 y) - 8y = 10

x= 2- 4y
-6 - 12y - 8y = 10

x = 2-4y
-20y = 16

x= 2-4y
y = -0,8

x = 2 - 4* (-0,8)
y = 0,8

x = 5,2
y = 0,8


x-2y=3
-2x+y=0

x = 3 + 2y
-2 (3 + 2y) +y = 0

x = 3 + 3y
-6 - 4y + y = 0

x = 3 + 3y
-3y = 3

x = 3 + 3y
y = -1

x = 3 + 3* ( -1)
y= -1

x = 0
y = -1
1 5 1
  • oki
  • Początkujący
2010-02-11T21:02:19+01:00
x=4y+2
3x - 8y =10

3(4y+2)-8y=10
x=4y+2

12y +6 - 8y =10
x=4y+2

12y-8y=10 -6
x=4y+2

4y=4 :4
y=1

x=4+2
x=6
y=1